The WTO's Doha negotiations and impasse : a development perspective - Khor, Martin (Third World Network PenangMY, 2007)
Notes that the multilateral trade negotiations held under the aegis of the World Trade Organisation Doha Work Programme have been touted as a 'Development Round' that will benefit the developing countries. Assesses the state of play of the negotiations and finds that development-oriented content is distinctly lacking in all the major subject areas covered viz. trade in agricultural and industrial products, services and the treatment of specific developing-country concerns such as the 'implementation issues' and 'special and differential treatment'.